2018
DOI: 10.2106/jbjs.17.00064
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Glenoid Morphology in Glenohumeral Osteoarthritis

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 20 publications
6
57
0
Order By: Relevance
“…Posterior humeral subluxation and glenoid retroversion was as well were related to posterior cuff ratio [21]. Moreover Aleem et al [21] did not find a correlation of glenoid inclination with rotator cuff muscle area whereas, Walker et al [24] and Donohue et al [23] described the association of increased posterior muscle fatty infiltration with posterior glenoid bone loss and glenoid retroversion, which is in line with our findings. Our data showed that posterior and posterosuperior glenoid wear was seen in 98% of patients with rotator cuff tears compared to only 91,5% in rotator cuff intact patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Posterior humeral subluxation and glenoid retroversion was as well were related to posterior cuff ratio [21]. Moreover Aleem et al [21] did not find a correlation of glenoid inclination with rotator cuff muscle area whereas, Walker et al [24] and Donohue et al [23] described the association of increased posterior muscle fatty infiltration with posterior glenoid bone loss and glenoid retroversion, which is in line with our findings. Our data showed that posterior and posterosuperior glenoid wear was seen in 98% of patients with rotator cuff tears compared to only 91,5% in rotator cuff intact patients.…”
Section: Discussionsupporting
confidence: 90%
“…The effects of glenoid version and inclination on rotator cuff integrity are not clearly established. Some recent studies focused on the relationship between rotator cuff integrity, fatty infiltration and glenoid deformity [21][22][23][24]. Increased glenoid retroversion was associated with a high crosssectional area of the supraspinatus and infraspinatus, rather than the low cross-sectional area of subscapularis [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior investigations with regard to rotator cuff muscle health in arthritic shoulders demonstrated some differences from our study. Walker et al attempted to determine temporal relationships in glenohumeral osteoarthritis 23 . In a series of 65 shoulders with CT scans at least 2 years apart and with known osteoarthritis, patients with initial posterior subluxation were more likely to progress to worsening deformity and to demonstrate a higher percentage of fatty infiltration in the rotator cuff compared with shoulders without subluxation.…”
Section: Discussionmentioning
confidence: 99%
“…For those glenoids that showed medialization, B-type glenoids showed more medialization over time than A-type glenoids. 38 In a follow-up study, Donohue et al analyzed 190 CT scans in 175 patients who underwent TSA for glenohumeral OA to assess the relationship of glenoid morphology and rotator cuff pathology. Using 3D CT and respective 2D images, pathologic glenoid version and joint line, modified Walch classification and Goutallier classification were determined.…”
Section: D Ct Characteristics Of the B2 Glenoidmentioning
confidence: 99%